Community programmes for coronary heart disease in Spanish primary care. (10th June 2014) - Frigola‐Capell, Eva; van Lieshout, Jan; Muñoz, Miguel A.; Verdú‐Rotellar, Jose; Orfila, Francesc; Suñol, Rosa; Wensing, Michel
SUMMARY: Objective: To explore the added value of community‐orientated programmes aimed at enhancing healthy lifestyles associated with the key components of cardiovascular risk management (CVRM) in coronary heart disease (CHD) patients. Methods: Observational study in Spain, including 36 practices, 36 health professionals, and 722 CHD patients (mean (SD) age 72 (11.73)). Our predictor variable of interest was reported deliveries from primary care practices (PCPs) concerning community‐orientated programmes such as physical exercise and smoking cessation groups. Data were obtained through structured questionnaires administered to PCP health professionals. Our CVRM outcome measures were as follows: recorded risk factors, drug prescriptions, and intermediate patient outcomes (blood pressure levels, low‐density lipoprotein cholesterol, and body mass index). Results: Thirty practices delivered community programmes: most delivered one [17 (47.2%) practices] or two [11 (30.5%) practices]. These educational programmes aimed to encourage enhanced healthy lifestyles through group counselling sessions, mailed print material, and one‐to‐one counselling. In PCPs delivering community programmes, more patients received antihypertensives (89.7%), antiplatelet therapy (80.5%), and statins (70.8%) than those PCPs without programmes, although there were no statistically significant differences between them. Conclusions: No evidence was found for the added value of community‐orientated CVRM programmes that could help health professionals refine criteria when including CHD patients in preventive programmes. Copyright © 2014 John Wiley & Sons, Ltd.